P127 Effect of depression and anxiety on health status and lung function in patients with alpha 1 antitrypsin deficiency. (December 2018) - Mobeen, F; Edgar, RG; Pye, A; Stockley, R; Turner, AM
Abstract : Introduction: Alpha-1 Antitrypsin deficiency (AATD) is a genetic condition that can lead to Chronic Obstructive Pulmonary disease (COPD). The psychological effects in patients with COPD have been investigated, although the psychological burden and contributing factors in patients with AATD are largely unknown. This study evaluated the prevalence of psychological disorders (anxiety and depression) in AATD and potential contributing factors. Methods: Retrospective analysis was performed on prospectively collected data from the UK AATD registry (1996–2018). Patients with severe deficiency (PiZZ/PiZnull) and sufficient data to calculate lung function (spirometry and gas transfer) and health status (HS) decline (≥four data points over ≥3 years) were identified and grouped as those with or without diagnosis of depression or anxiety. Univariate analyses were performed on a range of physiological, demographic and HS parameters, including (but not limited to) age, FEV1 % predicted and Saint George's Respiratory Questionnaire (SGRQ). All candidate variables were then put into a multivariable logistic regression. Similar analyses concerning the PiSZ genotype of AATD were also conducted. Results: Prevalence of anxiety or depression was 19% and was associated with lower baseline pulmonary function and worse HS in the PiZZ cohort (table 1). In univariate analyses we observed a greater rate of FEV1 % predicted decline per year (p=0.04) in those with depression or anxiety than those without (−1.08%; IQR −2.69-TO −0.29 AND, −0.90%–1.95-to −0.03 respectively) but no differences in SGRQ decline. In multivariable logistic regression differences in rates of FEV1 % predicted decline between the groups was maintained with each percent decrease in FEV1 % associated with a 1.17% increase in the odds anxiety or depression (coef −0.19 95% CI −0.31- to −0.07; p=0.002) when adjusted for baseline FEV1 % and SGRQ. There were no differences in the rate of decline of SGRQ between the two groups. Conclusion: These data suggest that disease progression, as measured by the rate of decline per year of FEV1, may be a major contributing factor to the prevalence of psychological disorders such as anxiety and depression in this cohort of PiZZ/Znull patients. This effect remains even after adjustment for baseline spirometry and HS.